Dentin hypersensitive: Ethiology and treatment - Utami, Nuryanni Dihin; Komara, Ira (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2015)
Dentin hypersensitivity is a response in exposed dentine with a symptom of clinically sharp and short pain. This condition may occur to exposed dentine due to gingival recession or enamel loss. Dentin hypersensitivity treatment aimed to either occlude the open dentinal tubules or block the neural response of the pulp. Invasive treatment are pulpectomy, restoration or surgery, while non invasive treatment are usually done by using tooth paste or mouthwash which is added by desensitizing agent